An Analysis of English Language Education (ELE) Students' Motivation in Learning Pedagogical Courses - Putu Yoga Sathya Pratama; I Gusti Ayu Lokita Purnamika Utami; Luh Diah Surya Adnyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Previous studies on motivation had been broadly researched, but little attention was given to learning pedagogical courses motivation. Thus, this qualitative research with case-study research design was conducted. This research aimed to describe ELE students’ motivation in learning pedagogical courses. The collecting data used were questionnaire, interview guidance, and human instrument. The obtained data were analyzed qualitatively through interactive data analysis. The result portrays there are more ELE students tend to be intrinsically motivated in learning pedagogical courses; the rest are identified to be extrinsically motivated, amotivated, and undefined motivation students. The reasons underlying their motivation in learning pedagogical courses can be categorized into: 1) internal reasons (mood, goals, passion, perspective, & personality) and 2) external reasons (parental, score, and lecturer).